Labour Market Integration and Equality for Disabled People: A Comparative Analysis of Nordic and Baltic Countries. (4th June 2017) - Kuznetsova, Yuliya; Yalcin, Betul; Priestley, Mark
Abstract: This article considers the employment situation of disabled people, and disability policies, in three Nordic and three Baltic countries (Denmark, Sweden, Norway, Estonia, Latvia and Lithuania). The analysis is framed by a changing paradigm for disability policy‐making, from compensation towards human rights and in a context of multi‐level governance involving the EU and UN as significant policy actors. The analysis draws on policy analysis and European social survey data to compare outcomes for disabled people in each country and in binary comparison between Nordic and Baltic countries. This enables interactions between individual and regional block factors to be modelled. We conclude that national policies make a difference, that non‐discrimination policies are not enough and that a focused mix of regulatory and redistributive measures is needed. The findings highlight better employment and social protection outcomes for disabled people in the Nordic countries, but point to policy challenges in both blocks. National processes of (de)commodification and stratification affect disabled people differently and this may disrupt our assumptions about welfare state comparisons.